AN ANALYSIS OF METADISCOURSE MARKERS IN ONLINE NEWS MEDIA: QUALITATIVE RESEARCH - Hastomo, Tommy; Aminatun, Dyah (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
This research aimed to investigate the function and category of metadiscourse markers employed in Tempo.co politic news articles. A qualitative method was applied in this current study for conducting the research. There are fourteen Tempo.co politic news articles as the sources of the data. The data are taken from the articles whose topic is Jokowi that had metadiscourse markers types. This current study found that there are 11 functions and 2 types in Tempo.co politic news articles. Interactional and interactive metadiscourse are the types of metadiscourse markers in this study. Moreover, the kinds of interactive metadiscourse observed in Tempo.co politic news articles are code gloss, evidential, frame marker, and transition. Meanwhile, engagement marker, attitude markers, booster, and hedges are the kinds of interactional metadiscourse observed in Tempo.co politic news articles. Nevertheless, this current study did not find self-mention and endophoric markers in the articles. The functions observed are addressing readers to include them or focus their attention into the discourse explicitly, showing the writer's or speaker's attitude towards the proposition, emphasizing or clarifying a statement, displaying the statements of the writers are more of a reasonable opinion than a fact, elaborating of what the writer has been written, exemplifying something in the discourse,  explicitly mentioning sources of information, establishing a clear dialog for readers, drawing a conclusion or countering ideas in the writerâ€™s statement, and adding an idea to the article.